Blood pressure dipping during REM and non-REM sleep in patients with moderate to severe obstructive sleep apnea - Ahmed S. BaHammam (Nature Portfolio, 2021)
Abstract A limited number of papers have addressed the association between non-dipping-blood pressure (BP) obstructive sleep apnea (OSA), and no study has assessed BP-dipping during rapid eye movement (REM) and non-REM sleep in OSA patients. This study sought to noninvasively assess BP-dipping during REM and non-REM (NREM)-sleep using a beat-by-beat measurement method (pulse-transit-time (PTT)). Thirty consecutive OSA patients (men = 50%) who had not been treated for OSA before and who had > 20-min of REM-sleep were included. During sleep, BP was indirectly determined via PTT. Patients were divided into dippers and non-dippers based on the average systolic-BP during REM and NREM-sleep. The studied group had a a median age of 50 (42–58.5) years and a body mass index of 33.8 (27.6–37.5) kg/m2. The median AHI of the study group was 32.6 (20.1–58.1) events/h (range: 7–124), and 89% of them had moderate-to-severe OSA. The prevalence of non-dippers during REM-sleep was 93.3%, and during NREM-sleep was 80%. During NREM sleep, non-dippers had a higher waist circumference and waist-hip-ratio, higher severity of OSA, longer-time spent with oxygen saturation < 90%, and a higher mean duration of apnea during REM and NREM-sleep. Severe OSA (AHI ≥ 30) was defined as an independent predictor of non-dipping BP during NREM sleep (OR = 19.5, CI: [1.299–292.75], p-value = 0.03). This short report demonstrated that BP-dipping occurs during REM and NREM-sleep in patients with moderate-to-severe OSA. There was a trend of more severe OSA among the non-dippers during NREM-sleep, and severe OSA was independently correlated with BP non-dipping during NREM sleep.